Meningkatkan Pengetahuan Kader Posyandu Tentang Pencegahan Stunting Pada Anak Melalui Aplikasi Mobile Learning Di Wilayah Kerja Puskesmas Cihaurbeuti - Wibowo, Daniel Akbar; Zen, Dini Nurbaeri; Sahrul Salam, Pebri Dais; Nuranisa, Nisa; Nurmalasari, Dewi; Fitriyani, Fitriyani (Yayasan Inspirasi El Burhani, 2024)
Background: Stunting is a major health problem affecting child growth in Indonesia. Posyandu cadres play a crucial role in preventing stunting through nutrition education but often face limitations in accessing information. At the Cihaurbeuti Health Center in Ciamis Regency, a mobile learning application can be an effective solution to enhance the knowledge of posyandu cadres. Objective: To enhance the knowledge of posyandu cadres on stunting prevention through a mobile learning application in the working area of Cihaurbeuti Health Center, Ciamis Regency. The method involves developing a mobile application that includes educational material on stunting prevention and training posyandu cadres to utilize the application. An evaluation is conducted to measure the improvement in cadres' knowledge and the effectiveness of the application compared to leaflets. Results: The results of the service showed a significant increase in knowledge after using the mobile learning application. The average knowledge score increased from 55% before training to 80% after training. The mobile learning application proved to provide interactive and easily accessible information. Knowledge application also improved, with posyandu cadres being more capable of providing accurate education to the community regarding stunting prevention. Conclusion: This program demonstrates that a mobile learning application is an effective tool for enhancing the knowledge of posyandu cadres and can serve as a model for other health education programs. It is expected to have a positive impact on stunting prevention and child health in Ciamis Regency